Transitional Functions: The Emergence of the Anticipatory Transition in Nineteenth-Century Sonatas - Luis Matos-Tovar (Current Musicology, 2023)
In sonata form, the transition module has specific primary functions and labels any other uncommon ones as deformations or, rather, idiosyncrasies. Considering the difference in compositional styles and techniques used between the eighteenth and nineteenth centuries, the latter undergoes a trend explored by some nineteenth-century composers: a development in its transition module, which ostensibly confining it to an idiosyncratic feature or a lower-level default of the transition (Hepokoski and Darcy, 2011). I argue that composers utilized this technique in transitions to foreshadow themes in subsequent modules, yielding an additional function of the transition. This paper examines nineteenth-century sonatas, providing an analytic overview of my findings and introducing a concept I call the “Anticipatory Transition,” offering an additional function to the transition–—distinct from other concepts by previous scholarship.